Metabolomic Profiling and Immunomodulatory Activity of a Polyherbal Combination in Cyclophosphamide-Induced Immunosuppressed Mice - Zahiruddin, Sultan; Parveen, Abida; Khan, Washim; Ibrahim, Mohammad; Want, Muzamil Y.; Parveen, Rabea; Ahmad, Sayeed (Frontiers in Pharmacology, 2022)
The study was aimed to develop a characterized polyherbal combination as an immunomodulator containing Phyllanthus emblica L., Piper nigrum L., Withania somnifera (L.) Dunal, and Tinospora cordifolia (Willd.) Miers.. Through response surface methodology (RSM), the ratio of aqueous extracts of four plant materials was optimized and comprised 49.76% of P. emblica, 1.35% of P. nigrum, 5.41% of W. somnifera and 43.43% of T. cordifolia for optimum immunomodulatory activity. The optimized combination showed antioxidant potential and contains more than 180 metabolites, out of which gallic acid, quercetin, ellagic acid, caffeic acid, kaempferitrin, and p-coumaric acid are some common and significant metabolites found in plant extracts and in polyherbal combination. Treatment of polyherbal combination with different doses in cyclophosphamide-induced immunosuppressed mice significantly (p < 0.01) enhanced the subsets of immune cells such as NK cells (60%), B cells (18%), CD4 (14%), and CD8 cells (7%). The characterized polyherbal combination exhibited potent immunomodulatory activity, which can be further explored clinically for its therapeutic applicability.